Skin aspects of COVID-19 - Skowrońska, Dagmara; Sak, Natalia; Hałasiński , Przemysław; Klamecki, Jakub; Jałowska, Magdalena; Kluzik, Anna; Kusza , Krzysztof (Journal of Medical Science, 2024)
Background: COVID-19 is a disease that has changed the realities of society, medical personnel, and patients around the world. The long-term course of the COVID-19 pandemic has allowed us to observe the many changes that are occurring in the course of this disease. Lesions resulting from SARS-CoV-2 infection manifest not only in the lungs but also in other systems, including the skin. Methods: The paper presents a comprehensive description of skin lesions occurring in the course of COVID-19 based on a literature review and own experience acquired in the intensive care unit. Results: The mechanism of formation of the cutaneous manifestations in SARS-CoV-2 infected patients as a result of the course of the disease was discussed. Skin lesions from the treatment, hospitalization and immobilization of the patient were also considered. The causes of developing bedsores are also highlighted, with examples provided with photographs. In addition, the paper includes tables comparing the appearance of skin lesions with the severity of the course and caused by pharmacotherapy, which may be a practical instrument in clinical practice. Conclusions: Cutaneous manifestations may be the single symptom of COVID-19, which may facilitate the diagnosis of this disease. It seems necessary to extend the diagnostics of skin lesions in the course of COVID-19 in order to understand their pathogenesis. Inadequate care due to staff shortages or inadequate education may lead to the development of pressure sores. It would seem imperative to implement solutions that could protect both patients and staff in the event of future pandemics.